Flux of Nutrient Leaching from Ultisol of Pineapple Plantation Ameliorated with FABA and Compost and Its Implications on Fertilizer Management - Nahdlia Putri Alayya; Iskandar Iskandar; Untung Sudadi (JOURNAL OF TROPICAL SOILS, 2026)
Ultisol is a weathered tropical soil order with low fertility status. It is also prone to nutrient leaching processes. Plantation area of PT. Great Giant Pineapple (PT GGP), grown in Ultisol, has been intensively cultivated for decades in rotation with banana and cassava. This study aims to evaluate the effects of FABA+compost amendment on nutrient leaching from the Ultisol in the PT GGP area and its implications for fertilizer management. A nutrient-leaching simulation was conducted using percolation experiments. Soil samples were taken from the 0-20 cm layer from pineapple-cultivated field plots 9 months after treatment application or 1 month before the plant regenerative-phase forcing step. Percolations were performed every 7 days with 170 mL Aquadest at 0.75 kg-1 soil for a 35-day experimental period, equivalent to the monthly average rainfall during the six wet months in the study area. The amelioration significantly reduced soil nutrient leaching, as indicated by tmax, total flux, and flux proportion. The band application of 25 t ha-1 FABA + compost gave the best results. The NO3 and K leaching flux proportions, however, were still high. It is suggested that controlled-release fertilizers be considered to reduce nutrient leaching flux.